Nilai Sosial Dalam Legenda Bulusan Sumber Kudus - Antika, Silfi; Lindi, Adzin Eka; Aryani, Dias Syifa; Muti'ah, Izzatul; Mohammad Kanzunnudin (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
Folklore is a story that develops in the community and is spread orally that has a moral message. Legend is part of folklore that tells the history of a place. There are several legends in an area, in the Central Java area of ​​Kudus City there is one Legend, namely the Bulusan Legend. This research is a Qualitative study with a descriptive narrative type and content analysis method. This study aims to analyze the social values ​​in the book "Cerita Rakyat Pesisir Timur" by Mohammad Kanzunuddin about the Bulusan Legend. The qualitative approach technique provides an explanation of the hidden meaning in the legend text in depth and contextually. The data used are written facts in the form of books and journal articles. The results of the social value of the Bulusan legend, namely the story of the curse of Mbah Dudo and his students who turned into bulus show noble life values. The analysis reveals various moral teachings that are useful as social values ​​such as loyalty, cooperation, and common interests embedded in this legend.